Sedimentology and geochemistry of tufa and their relation to hydrochemistry of springs: An example of Abgarm Tufa of Kalat- east of Kopet- Dagh basin - Fatemeh Goleij (Journal of Stratigraphy and Sedimentology Researches, 2017)
Tufa is the non- marine carbonates that formed from cold to low temperature freshwater at low depth and low energy flow conditions. Abgarm’s tufa is a typical kind of these deposits. Field and microscopic studies led to recognize of seven allochthonous and autochthonous lithofacies. The presence of dense plant covering river margins, increasing use of dissolve CO2 in water and providing chemical conditions due to turbulence are factors that are important in the formation of tufa. Based on concentrations of dissolved ions, the type of Abgarm water is Ca- Mg- HCO3. Based on ions ratio, the water with primary meteoric origin is affected by passing through dolomitic limestone and evaporite of the Mozduran and Shurijeh formations. The high concentrations of these ions caused the carbonate to be trapped between algae filamentous and formed a kind of active tufa. The presence of gastropod species show a dominance wet climatic conditions when these deposits formed. At the next step, decreasing rainfall and increasing temperature and evaporation, caused the death of two gastropods species (Melanopsis praemorsa and Galba truncatula) in the studied area. Isotopic analysis of oxygen and carbon show the effects of meteoric waters and Mozduran aquifer limestone formation in isotopic compositions of tufa in Abgarm area.